(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
When health inequalities constitute inequity? We can say when they derive from the unequal distribution of power, income, goods and services, at a global and national level. The immediate consequences of unfairness are visible in people’s living and working conditions, in access to health care, to education, in the possibility of leading a dignified life. This unequal distribution of health-damaging experiences is by no means a "natural" phenomenon, but it is the result of a combination of bad social policies and ineffective programs to contrast poverty, unfair economic agreements and bad policies. Together, the structural determinants and conditions of everyday life are the social determinants of health and are responsible for an important part of health inequalities between and within countries. The article, starting from a tentative definition of health inequalities, reviews the main factors associated to health inequalities with examples from the Italian context. Once explained the mechanisms that may cause health differences in the population, some possible contrasting actions are proposed in terms of health and social policies.